Overview of pleiotropic effects of platelet P2Y12 receptor inhibitors - Adamski, Piotr; Koziński, Marek; Ostrowska, Małgorzata; Fabiszak, Tomasz; Navarese, Eliano Pio; Paciorek, Przemysław; Grześk, Grzegorz; Kubica, Jacek (Thrombosis and Haemostasis, 2014)
Dual antiplatelet therapy consisting of one of the P2Y12 receptor inhibitors in conjunction with aspirin is the mainstay of treatment for patients with acute coronary syndromes (ACS) and those undergoing percutaneous coronary interventions (PCI). In recent years, multiple extra-platelet features of P2Y12 receptor antagonists have been reported in numerous clinical trials. The aim of this review is to summarise reported pleiotropic effects of clopidogrel, prasugrel, ticagrelor and other P2Y12 receptor blockers. We included observations made both in human and in animal models, together with proposed mechanisms of action for described features. If confirmed in randomised studies and properly applied to everyday practice, the observed extra-platelet actions could enable us to improve efficacy of ACS and post-PCI treatment, as well as to confine mortality and occurrence rate of cardiovascular events.
Keywords: Clopidogrel; off-target effect; P2Y12 receptor; prasugrel; ticagrelor